2013
DOI: 10.1270/jsbbs.63.104
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a wheat (<i>Triticum aestivum</i> L.) mutant in ABA 8′-hydroxylase gene: effect of reduced ABA catabolism on germination inhibition under field condition

Abstract: Pre-harvest sprouting, the germination of mature seeds on the mother plant under moist condition, is a serious problem in cereals. To investigate the effect of reduced abscisic acid (ABA) catabolism on germination in hexaploid wheat (Triticum aestivum L.), we cloned the wheat ABA 8′-hydroxyase gene which was highly expressed during seed development (TaABA8′OH1) and screened for mutations that lead to reduced ABA catabolism. In a screen for natural variation, one insertion mutation in exon 5 of TaABA8′OH1 on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 32 publications
1
43
0
Order By: Relevance
“…Similar to what was observed in imbibed barley grains, TaABA8'OH2 expression remained at a very low and stable level in both in D and AR grains [16]. The above expression analysis conducted upon imbibition of AR and D grains of wild wheat as well as the examination of the double wheat mutant in the TaABA8'OH1 gene demonstrates that research involving manipulation of the TaABA8'OH1 gene may contribute to solving the problem of pre-harvest sprouting of cereal grains [15,31]. However, recent report indicate that AR mediated wheat dormancy release might be associated with changes in ABA signaling and sensitivity without affecting the metabolism of this phytohormone, since there were no significant differences in expression of ABA metabolic genes between D and AR wheat grains, even after imbibition [24].…”
Section: Effect Of After-ripening On Aba Metabolismsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar to what was observed in imbibed barley grains, TaABA8'OH2 expression remained at a very low and stable level in both in D and AR grains [16]. The above expression analysis conducted upon imbibition of AR and D grains of wild wheat as well as the examination of the double wheat mutant in the TaABA8'OH1 gene demonstrates that research involving manipulation of the TaABA8'OH1 gene may contribute to solving the problem of pre-harvest sprouting of cereal grains [15,31]. However, recent report indicate that AR mediated wheat dormancy release might be associated with changes in ABA signaling and sensitivity without affecting the metabolism of this phytohormone, since there were no significant differences in expression of ABA metabolic genes between D and AR wheat grains, even after imbibition [24].…”
Section: Effect Of After-ripening On Aba Metabolismsupporting
confidence: 63%
“…ABA conjugation is reversible, and the hydrolysis of ABA glucosyl ester (ABA-GE) is catalyzed by β-glucosidases (BG). [16,31,72] Tab. 1 Potential genes participating in ABA synthesis and catabolism in cereals.…”
Section: Effect Of After-ripening On Aba Metabolismmentioning
confidence: 99%
“…The QPhs.spa-6D QTL, detected in field and GH environments, mapped in the interval gwm325-cfd80 which is near the location of the germination inhibitor phytohormone ABA responsiveness gene TaABA8 0 OH1 (ABA 8 0 -hydroxylase activity) on chromosome 6D. The gene plays a key role in seed dormancy regulation (Kobayashi et al 2010;Chono et al 2013;Iehisa et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…3), which contains a region that we could not sequence using the BigDye Terminator v 3.1 Cycle Sequencing kit (Life Technologies, Carlsbad, CA, USA), likely due to long repeated regions. However, we could sequence 529 bp and 142 bp sequences on either side of the inserted fragment; homology searches showed that these sequences perfectly match a previously reported transposable element (accession number AB736318), which inserted in a wheat abscisic acid 8 0 -hydoxylase gene (TaABA8 0 OH1-D) (Chono et al 2013). Thus, we think that the undetermined sequence likely has the same sequence as the corresponding part of the transposable element.…”
Section: Analysis Of Sequences Not Amplified By the Caps Markermentioning
confidence: 56%